ANGKA HARAPAN HIDUP DI ERA DESENTRALISASI (KABUPATEN/KOTA JAWA BARAT) - Wardhana, Adhitya; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.05.TAHUN 2020, 2020)
This study aims to explains the development of life expectancy (AHH) in West Java Regency / City. Variable of life expectancy in this study is influenced by income (GRDP), access to clean water, mean of years schooling and poverty. The scope of the study was separated into two regional classifications in West Java that were in a condition of life expectancy under the age of 71 and 72 years. The research method used is the panel data method and The Generalized Least Square (GLS) model. The results of this study explain the variable income (GRDP), access to clean water and mean of years schooling have a positive and significant effect on AHH under the age of 71 years. Meanwhile, the independent variables that have a positive and significant influence on life expectancy below 72 years are income (GRDP) and poverty. Income variable (GRDP) becomes an independent variable that affects AHH at age 71 and 72 years.